Pengembangan UKBM Interaktif Flipbook dengan Canva pada Mapel Bahasa Inggris Materi Discussion Text di SMA Negeri 2 Blitar - Widi Astuti; Atiqoh Atiqoh; Hari Karyono (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The objectives of this thesis are (1) to produce an interactive UKBM Flipbook product with Canva in the English subject for Discussion Text Materials at SMA Negeri 2 Blitar. (2) find out the feasibility of interactive UKBM Flipbook with Canva in the English subject Discussion Text material at SMA Negeri 2. This development uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) From the results of the study, data was obtained that at the expert validation stage which was divided into Material Expert Validation by 95%, Media Expert validation by 85% and Design Expert Validation by 93%. If it is converted into the validity criteria adapted from Sugiyono (2011: 93) and very valid criteria are obtained for material validation, valid from Media experts and very valid by Design experts. So that as a whole the product development in the form of UKBM Interactive Flipbook with Canva in English subject, Discussion Text material, is very valid and feasible to use. Meanwhile, the results of the data analysis from the product trial showed that the percentage level of module validity was 88% with very valid criteria for 10 students as small group test respondents. Meanwhile, in the large group trial, the average percentage of module validity was 87% with very valid criteria for 33 students as respondents. It can be concluded that this interactive UKBM flipbook with Canva is very practical to use in learning English for Class XII Discussion text materia.